ANALISA KINEMATIK, DINAMIK DAN METODE GERAK KAKI MODEL SNOOPER HEXAPOD ROBOT - Munadi, Munadi; Haryanto, Ismoyo; Prahasto, Toni (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2015)
This article presents how to make a model of snooper hexapod robot as a legged robot which is inspired by the spider. This model robot is used for monitoring systems of an industrial area. We design an hexapod robot that consists of 18 dof, which it used acrylic as a base material, servomotor as a driver and an ATmega 128 as microcontroller. Â We start to make a mechanical design of a snooper hexapod robot construction. Furthermore, kinematics and dynamics analysis of hexapod robot is discussed using Matlab from the control point of view. The objective of kinematic analysis is to determine the kinematic quatities such as displacements, velocities, and accelerations of the elements of model robot when the input motion is given. It establishes the relationship between the motions of various components of the link. The dynamics analysis will inform a torque at the joint ankle hexapod robot using modeling Matlab Simmechanics. The model of hexapod robot is used for monitoring systems so called snooper hexapod will be designed and manufactured so have the required capabilities as a surveillance robot that is able to reach the difficult area and can transmit visual information to the operators who control it. Analysis is done on the robot motion algorithm on three kinds of methods of walk (one wave, two wave, and tripod) with few parameters specified